2008
DOI: 10.1093/sleep/31.3.419
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Disordered Breathing in the Usual Lifestyle Setting as Detected with Home Monitoring in a Population of Working Men in Japan

Abstract: The prevalence of moderate to severe SDB (RDI > or = 15) was 22.3% in this Japanese male working population aged 23 to 59, measured in participant's usual life settings. Unattended home monitoring with type 3 portable monitors and actigraphy was highly reliable and may be suitable for analyzing SDB in the usual lifestyle setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 25 publications
4
80
2
1
Order By: Relevance
“…The recognition of sleep apnea syndrome (SAS) as a common and serious public health problem has become widespread, and the prevalence of SAS in the Japanese male working population has increased during the past decade, being recently estimated at 22.3% (Hida 1998, Nakayama-Ashida et al 2008. SAS has conventionally been divided into two categories: obstructive sleep apnea syndrome (OSAS) and central sleep apnea syndrome (CSAS) including CheyneStokes respiration.…”
Section: Study Subjectsmentioning
confidence: 99%
“…The recognition of sleep apnea syndrome (SAS) as a common and serious public health problem has become widespread, and the prevalence of SAS in the Japanese male working population has increased during the past decade, being recently estimated at 22.3% (Hida 1998, Nakayama-Ashida et al 2008. SAS has conventionally been divided into two categories: obstructive sleep apnea syndrome (OSAS) and central sleep apnea syndrome (CSAS) including CheyneStokes respiration.…”
Section: Study Subjectsmentioning
confidence: 99%
“…Therefore, it is likely that many people with OSAS remain undiagnosed. 11,12 Nocturia is another multifactorial disorder that can be caused by hypertension, diabetes, heart failure, or sleeping disorders. 13,14 OSAS can be an underlying cause of nocturia, although it is infrequently recognized, even in the field of urology.…”
Section: Introductionmentioning
confidence: 99%
“…3,9 The result of this study demonstrated higher sleep BP in SAS patients with CKD compared with those without CKD, even though the severity of SAS was similar. This result suggested that SAS and CKD might synergistically induce nocturnal hypertension, which probably increases the risk of onset of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 58%
“…2 Nocturnal hypertension and morning BP surge are induced by sleep disordered breathing, which can be observed in 22% of Japanese adult males. 3 Typical clinical features of BP changes in patients with sleep disordered breathing and those with sleep apnea syndrome (SAS) are nocturnal hypertension and non-dipper patterns of circadian BP. As the severity of SAS increases, sleep BP is elevated even in a patient whose BP is within the normal range in the clinic.…”
mentioning
confidence: 99%